Analgesia and sedation for intratracheal intubation in the neonatal period: an integrative literature review - Naujorks, Silvia; Knob, Gabriele H. [UNESP]; Dotto, Patrícia P. [UNESP]; Henn, Roseli; Zamberlan, Cláudia (Elsevier, 2023)
Objective: to assess evidence available in the literature about the use of sedation and analgesia for intratracheal intubation of newborns. Data sources: by means of an integrative literature review, the authors looked for evidence related to the theme from the last ten years, indexed in the Pubmed, Medline, Lilacs, Scielo, and Scopus databases, by combining the descriptors: newborn, intratracheal intubation, and analgesia. Articles in Portuguese, English, and Spanish that met the research purpose were included. Data summary: After applying the eligibility criteria, ten articles on the topic were obtained, predominantly narrative reviews, retrospective studies, observational studies, and only one non-randomized clinical trial, which characterizes the literature related to the topic as having a low level of scientific evidence. There is still no consensus in the literature on which medications and indications are for use in non-elective intubations, despite the ethical recommendation. Discussion: pain and its deleterious effects should not be neglected. Neonatal Intensive Care Units should have their own protocols regarding sedation and analgesia for intubation considering the individual characteristics of each patient. There is an ethical recommendation regarding the use of sedation and analgesia for intubation since it is a known painful procedure.
Keywords: Intratracheal intubation; Newborn; Pain